ANALISIS MODEL PENERIMAAN TEKNOLOGI SIMPUS E-HEALTH DI PUSKESMAS KABUPATEN BANTUL, YOGYAKARTA - Ignatius Djuniarto (STIKES Wira Husada Yogyakarta, 2019)
ABSTRACT The technology of Primary Health Care (PHC) Management InformationSystem (Indonesian: Sistem Informasi Manajemen Puskesmas – SIMPUS)e-health in PHC Bantul Regency, Yogyakarta, had facing obstacles in itsapplication. Some users said that SIMPUS e-health was incomplete infeature, time consuming and not supported by PHC facilities, thus affectingthe attitude and interest to use it. The aim of this research was to proveSIMPUS e-health is useful, easily use, influencing attitudes and interesting tobe used in PHC Bantul Regency, Yogyakarta.Methods: The research was quantitative confirmatory. The population in thisresearch was the employee of PHCs in Bantul Regency, Yogyakarta, whohad actively used SIMPUS e-health facilities as many as 110 people with 86respondents as samples. Data analysis for this research was descriptionstatistics and regression analysis. The result of the study showed that (1)perceived usefulness had significant influence on behavioral intention to useSIMPUS e-health, this was indicated by Sig.value = 0.004 < 0.05 (2)perceived ease of use had significant influence on behavioral intention touse SIMPUS e-health, this was indicated by Sig. value = 0.005 > 0.05 (3)attitude towards SIMPUS e-health using had a significant influence onbehavioral intention to use SIMPUS, this was indicated by Sig.value = 0,013< 0.05 (4) Perceived usefulness, perceived ease of use and attitude towardSIMPUS e-health using simultaneously had significant influence onbehavioral intention to use SIMPUS e-health, this was indicated by Sig.value = 0.000 < 0.05. Conclusion: (1) perceived usefulness had significantinfluence on behavioral intention to use SIMPUS e-health (2) perceived easeof use had significant influence on behavioral intention to use SIMPUS ehealth(3) attitude toward using had significant influence on behavioralintention to use SIMPUS e-health (4) Perceived usefulness, perceived easeof use and attitude toward SIMPUS e-health using simultaneously hadsignificant influence on behavioral intention to use SIMPUS e-health.